Agile Supply Chain: Competing Through Competitive Excellence - Lina Anatan (Universitas Islam Indonesia, 2006)
Global competition characterized by changing customer and technological re-quirement. To cope with this instability conditions, companies need to focus on cost and qual-ity advantage. They are undergoing business efficiency and effectiveness through reassessing internal business operation such as purchasing, warehousing, material management and dis-tribution. Speed, quality, and flexibility are being emphasized as a competitive excellence of responding to the customer’s need. To become more responsive to the needs of customer and market require more than speed, it also requires a high-level maneuverability that has come to be the term agility. Agility in supply chain is one of the solutions to achieve competitive advan-tage as it provides many opportunities for reducing operating cost and improving customer service and satisfaction. In other words, the agility of a supply chain shown how well the rela-tionships involved in the processes mentioned enhance the objectives of agile manufacturing. These objectives are customer enrichment ahead of competitors, achieving mass customization at the cost of mass production, mastering change and uncertainty through routinely adaptable structures, and leveraging the impact of people across enterprises through information tech-nology.Keywords: leanness, agility, agile supply chain, competitive excellence